THE ADVANTAGES AND BARRIERS OF THINK PAIR SHARE TECHNIQUE IN READING COMPREHENSION ACHIEVEMENT IN EFL CLASS: A REVIEW - Arif Alexander Bastian; Rizki Anugrah Putri Rahayu (Universitas Aisyah Pringsewu, 2023)
The goals of this research are twofold: (1) to learn more about the benefits of adopting TPS, and (2) to identify the challenges that arise when using TPS to the development of reading abilities and provide potential solutions to them. Cooperative learning is one of several effective pedagogical approaches that may be used to instruct students in reading. The Think-Pair-Share method is one kind of collaborative education. This research shows the ups and downs of using the Think, Pair, Share technique in EFL reading instruction. TPS allows students to work both alone and in groups, provided they follow the methods provided. TPS identifies the text's message in pairs to facilitate student comprehension. Using this method, kids may be engaged, motivated, and ultimately successful in their reading comprehension. However, TPS has a few limitations that hinder reading comprehension. Some pupils don't pay attention since they know they can talk about anything else with their companion other than the assigned material. Then, pupils who aren't well-versed in the material (the questions) are more inclined to cheat for their partners. Teachers may help students overcome these difficulties by choosing engaging subjects and pairing them together effectively.